THE ROLE OF BRAND TRUST IN MEDIATING BRAND IMAGE AND PRODUCT INNOVATION ON CONSUMER LOYALTY (STUDY ON SAMSUNG USERS IN SURAKARTA) - Wardhani, Mahartiwi Kusuma; DPW, Ida Aryati; Sudarwati, Sudarwati (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
This research aims to investigate the influence of brand trust as a mediating factor between brand image, product innovation, and consumer loyalty. The study encompasses an infinite number of consumers in Surakarta, with a sample size of 100 respondents selected through purposive sampling. Primary data were collected using a questionnaire. The findings reveal that brand image positively and significantly impacts consumer loyalty, while product innovation lacks a significant effect on consumer loyalty. Additionally, brand trust exhibits a positive and significant influence on consumer loyalty. Furthermore, brand image positively and significantly affects brand trust, as does product innovation. The study also indicates that brand image positively and significantly influences consumer loyalty through brand trust, and similarly, product innovation has a positive and significant impact on consumer loyalty through brand trust. Keywords: Brand Trust, Brand Image, Product Innovation, and Consumer Loyalty.